2022
DOI: 10.3389/fmars.2022.753325
|View full text |Cite
|
Sign up to set email alerts
|

Cyclone Impacts on Coral Reef Communities in Southwest Madagascar

Abstract: Tropical cyclones can cause severe destruction of coral reefs with ecological consequences for reef fish communities. Ocean warming is predicted to shorten the return interval for strong tropical cyclones. Understanding the consequences of cyclone impacts on coral reefs is critical to inform local-scale management to support reef resilience and the livelihood security of small-scale fishing communities. Here, we present the first analysis of a tropical cyclone disturbance on coral reefs in Madagascar. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Thermal stress in 2001, 2006, 2009, and 2021 (Figure S1) has likely caused mild effects on coral assemblages of the GRT, but no mass bleaching events were reported. Cyclones are less frequent in the southwest coast of Madagascar compared to the eastern coast or to other regions in the SWIO, and though Cyclone Haruna passed 120 km north of Toliara in February 2013 (Carter et al., 2022), no significant impacts on the GRT were reported. Similarly, outbreaks of the coral predator Acanthaster spp.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thermal stress in 2001, 2006, 2009, and 2021 (Figure S1) has likely caused mild effects on coral assemblages of the GRT, but no mass bleaching events were reported. Cyclones are less frequent in the southwest coast of Madagascar compared to the eastern coast or to other regions in the SWIO, and though Cyclone Haruna passed 120 km north of Toliara in February 2013 (Carter et al., 2022), no significant impacts on the GRT were reported. Similarly, outbreaks of the coral predator Acanthaster spp.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclones are less frequent in the southwest coast of Madagascar compared to the eastern coast or to other regions in the SWIO, and though Cyclone Haruna passed 120 km north of Toliara in February 2013 (Carter et al, 2022), no significant impacts on the GRT were reported. Similarly, outbreaks of the coral predator Acanthaster spp.…”
Section: Study Area and Sampling Stationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In recent decades, these reefs have been impacted by the bleaching event of 1998 [ 70 , 76 ], and 2016 [ 77 ] ( S1 Table ). The major cyclones that had a potential impact on coral assemblages are Haruna at Salary Nord in 2013, Enawo 2017 at Masoala and Nosy-Be in 2017, and Belan at Nosy-Be in 2019 [ 78 ]. However, the impact of these disturbances on coral assemblages in our three regions has not been quantified.…”
Section: Methodsmentioning
confidence: 99%